Internal Migration and Severity of Domestic Violence in Nepal - Rai, Mahendra Kumar (Curriculum Development Journal, 2024)
Domestic violence is a grave violation of human rights. The incidences and severity of domestic violence have not reduced at an expected level despite having legal and policy provisions in Nepal. The main objective of this paper is to assess the effects of internal migration on physical, sexual, and emotional violence against women in Nepal. This study applied the data set of Nepal Demographic and Health Survey 2022 which encompassed 3,172 women aged 15-49 years. The univariate, bi variate, and logistic regression in multivariate analysis was employed for rigorous data analysis. Despite increasing the volume of internal and external migration, the level and severity of domestic violence have not been reduced as expected. The analysis of this study revealed that the impact of migration is significant for reducing physical, sexual, and emotional violence. The findings of the study demonstrate that domestic violence against women has increased with the increment of the duration of stay whereas the incidences of domestic violence are observed to decrease in the migration stream from rural-to-rural migration. The likelihood ratio of experiencing domestic violence by women is observed increasing with the increment of duration of migration means a shorter duration of stay is significantly associated with a lower likelihood of experiencing domestic violence whereas the likelihood ratio of domestic violence is observed decreasing with increasing the age of women.